Pretreated aluminium dross waste as a source of inexpensive alumina-spinel composite ceramic hollow fibre membrane for pretreatment of oily saline produced water - Aziz, Mohd Haiqal Abd; Othman, Mohd Hafiz Dzarfan; Hashim, Nur Awanis; Rahman, Mukhlis A.; Jaafar, Juhana; Hubadillah, Siti Khadijah; Tai, Zhong Sheng (Elsevier, 2019)
Pretreatment of produced water using ceramic membrane is considered promising due to its excellent separation performance and thermal and mechanical stabilities, however, the high cost of ceramic membranes discourages industries for large scale applications. The purpose of this work is to fabricate ceramic hollow fibre membranes from alumina-spinel composite powder synthesized from low-cost aluminium dross waste for the pretreatment of oily saline produced water. The hollow fibre membranes were prepared via phase inversion-based extrusion and sintering technique. Aluminium dross (less than 50 µm) was subjected to pre-treatment via water leaching and calcination, resulting in alumina (Al2O3) and spinel (MgAl2O4) as major constituents. Subsequently, the as-prepared alumina-spinel composite powder was used as a ceramic material in fabricating the hollow fibres. The effect of sintering temperatures on the morphology, crystalline phase, pore size and porosity, mechanical properties, and removal efficiencies of the alumina-spinel composite hollow fibre membranes were investigated. The microfiltration test of the hollow fibres was assessed using produced-water feed of 200 mg L−1 at 1 bar. The hollow fibre sintered at 1275 °C offers 92.41% rejection percentage of oil, the highest after 50 min of stable flux. Furthermore, turbidity was found to decrease from 378 NTU to 28.5 and 22.5 NTU for hollow fibres sintered at 1250 and 1275 °C after 2 h of filtration. In this work, the alumina-spinel composite hollow fibre membranes are found to be an effective tool as an alternative for the pretreatment of oily saline produced water.